The Competitiveness of Indonesian Cocoa Product and Their Derivates in the International Market - Baroh, Istis (Proceedings International Conference on Sustainable Innovation (ICoSI), 2022)
This study aims to analyze the competitiveness ofIndonesian cocoa between its several derivate products from 2006to 2015 of two importing countries. Germany and The USA arechosen as the representative of the international markets becauseof three reasons. First, those two countries are the mostprospective markets of cocoa products. Second, they consumelarge amount of cocoa processing products for their Industries.Third, as the core players of trade, they always import processedcocoa producs from Indonesia in the pastdecade. We use RevealedComparative Advantage (RCA) approach to analyze thecompetitiveness of processed cocoa products, followed byRevealed Symmetric Comparative Advantage (RSCA) approachto avoid upward-biased problems from the previous steps. RSCAenables us to manipulate the RCA index to be symmetrical withinterval values between -1 and +1 (Prasad, 2004). The resultsshowed that in Germany, cocoa paste products and cocoa butterthe two products that have high competitiveness, whereas cocoapowder was not competitive. In the USA, Indonesian cocoa butterwas competitive while cocoa paste and cocoa powder were notcompetitive. Indonesia should focus on cocoa paste and cocoabutter to maintain their competitiveness through pricing, contractnegotiations, and trade relations